Nirmala and Banhatti-Sombor Index over Tensor and Cartesian Product of Special Class of Semigroup Graphs - Seda Oğuz Ünal (Journal of Mathematics)
The Nirmala and first Banhatti-Sombor index which is originated from Sombor index is designated by NG=∑uv∈EGdu+dv and BSO1G=∑uv∈EG1/du2+dv2, respectively. In this work, we calculated the Nirmala and Banhatti-Sombor index over the tensor and Cartesian product of a graph of an algebraic structure by presenting two different algorithms.